Law and judicial duty - Hamburger, Philip, 1957- (Harvard University Press, 2008)
"Almost every day, a judge in the United States holds a statute unconstitutional. This power of the judges is known as "judicial review," and it often seems the central feature of American constitutional law. The authority and scope of this power, however, have long remained unclear, and because historical accounts have tended to suggest that the judges themselves largely developed judicial review, the history has given credence to the view that judges enjoy considerable discretion over the extent and exercise of this power.